Functional Reconstruction with Latissimus Dorsi Flap following Resection of an Extensive Basal Cell Carcinoma in the Shoulder Region: A Case Report - Paprottka, Felix J.; Klimas, Dalius; Hebebrand, Detlev (The Surgery Journal, 2018)
Large and ulcerating skin tumors have become a rarity in the modern Western world. However, these conditions can cause serious life-threatening complications. The case of a 60-year-old male Caucasian patient is reported, who had suffered from an extensive basal cell carcinoma in the right shoulder region for several years. The patient kept the lesion secret from his friends and family and delayed presentation to health care services. After an episode of tumor-related heavy bleeding, the patient was referred to our clinic and received a radical surgical tumor resection—followed by defect coverage with a latissimus dorsi myocutaneous flap. An alternative treatment option that could be offered to the patient would have been a mutilating surgical procedure with an arm amputation. By using this plastic reconstructive surgical technique, the main function of the shoulder joint was conserved. The presented case demonstrates options for defect coverage of problematic wounds in anatomically complex body regions—like the shoulder—by using a functional reconstruction using myocutaneous flaps.
Keywords: basal cell carcinoma; shoulder defect; functional reconstruction; latissimus dorsi myocutaneous flap